Implementation Of Strategies Towards Problem Credit Settlement at PT. BPR Laksana Abadi Sunggal Medan - Pontianus P Sarumaha; Tri Sastraman Farasi; Hesti Mariani Zega; Feby Vantina Hutagalung; Nalom Siagian; Patricia Herpayanti Rajaguguk (International Journal of Community Service (IJCS), 2025)
This internship was carried out by students of the Business Administration Study Program, Faculty of Social and Political Sciences, HKBP Nommensen University Medan, at the branch office of PT. Laksana Abadi Sunggal People's Economic Bank (BPR), located at Jl. Mustafa No. 58, Medan, North Sumatra. This bank focuses on serving the local community as well as Micro, Small, and Medium Enterprises (MSMEs), with its main function being to collect funds from the public and redistribute them in the form of credit. The internship aims to identify the factors that contribute to non-performing loans among the customers of PT. BPR Laksana Abadi Sunggal, to analyze the strategies and measures implemented by the bank, and to identify the challenges encountered in the process of resolving problematic loans, along with finding appropriate solutions. Through this internship, students of the Business Administration program are given the opportunity to learn and understand the procedures for resolving non-performing loans.This internship activity is expected to serve as a sustainable effort to enhance students' knowledge regarding problematic credit. By conducting their internship at PT. BPR Laksana Abadi Sunggal, students gain increased understanding of non-performing loans. The success of this internship depends on an integrated approach. Based on this foundation, the internship program at PT. BPR Laksana Abadi Sunggal has the potential to provide significant benefits for students in understanding credit resolution processes and to contribute to strengthening the financial stability of PT. BPR Laksana Abadi Sunggal